(untitled) (Texas Journal of Philology, Culture and History, 2023)
Historiography is a science that studies and analyzes the formation and development of historical knowledge, historical products or historical research created at a certain historical stage. Historiography regularly deals not only with history, but also with special historical sciences. The main task of historiography is to deeply and objectively understand the development process of history, analytically apply the historical knowledge accumulated during a certain historical period, and to understand the current problems of history and prevent future mistakes. This article describes the formation of historical knowledge and the essence of historiography in Central Asia, the unparalleled work of rulers and scholars who contributed to it.